High carbohydrate intake increases risk of coronary heart disease in adults: a prospective cohort study - Darjoko, Sulistyowati Tuminah; Wahyuningsih, Tri; Sudikno, Sudikno (Universa Medicina, 2019)
BackgroundCoronary heart disease (CHD) ranks second after diabetes mellitus (DM) based on hazard rate, and after stroke (based on number of deaths caused). Our aim was to determine the risk factor and magnitude of CHD among adults. Methods A cohort study on risk factors of non-communicable diseases (CS-RFNCD) was conducted on subjects aged ≥25 years. Initiated by screening, follow-up (FU) was done 3 times yearly and complete health examination every 2 years. CHD cases screened by electrocardiographic examination on subjects aged ≥40 years and <40 years with history of hypertension and/or heart disease. Screening results found 840 of 5690 subjects with CHD diagnosis who were excluded from cohort study sample. Non-CHD subjects and those aged <40 years without a history of hypertension and/or heart disease, totalling 4840 people, were included in study sample and followed up for 6 years. Data were analyzed using Cox regression.ResultsCarbohydrate intake of ≥60% of total energy had a 2.8-fold higher CHD risk [HR=2.790; 95% CI: 1.962 - 3.967; p=0.000] than that of an intake of <60% of total energy. Age of ≥55 years had 2.6-fold higher CHD risk [HR=2.573; 95% CI: 1.803 - 3.671; p=0.000] than age of <55 years. Blood total cholesterol of ≥200 mg/dL had 1.9-fold higher CHD risk [HR=1.893; 95% CI: 1.319 - 2.715; p=0.001] than that of <200 mg/dL.ConclusionHigher intake of carbohydrate increases CHD incidence among adults. Efforts in controlling CHD risk factors are still needed especially in consumption behavior through a family approach.